Analisis Pengetahuan dan Sikap tentang Pengaruh Seks Pranikah pada Remaja Putri di SMAN 2 Muara Sabak Timur - Barokah, Ummi; Sulastri, Sulastri; Riya, Rosa; Putri, Aristy Rian Avinda (Jurnal Akademika Baiturrahim Jambi, 2025)
Adolescent reproductive health is a healthy condition related to organ systems, functions and reproductive processes that occur in adolescents who are not only free from disease and disability, but are also mentally, socially and culturally healthy. The aim of this research was to determine the influence of knowledge and attitudes about primatial sex on class XII female students at State High School 2 Muara Sabak Timur. The research design used was a one group pre-posttest design. The research location is State High School 2 Muara Sabak Timur in March 2024. The population is 115 class XII female students. The sampling technique using the Slovin formula obtained 53 female students, in accordance with the inclusion and exclusion criteria. Data were collected using a questionnaire which was filled out by respondents after obtaining informed consent. Data analysis using t-test. Before the counselling was carried out, the majority of respondents had poor knowledge as many as 43 people (81.1%) and negative attitudes as many as 52 people (98.1%), but after the counselling was carried out the majority of respondents had good knowledge as many as 51 people (96.2%), and a positive attitude of 53 people (100%).There is an influence of counselling about premarital sex on the knowledge and attitudes of class XII female students at State High School 2 Muara Sabak Timur.